Consumer agency in cannabis supply - Exploring auto-regulatory documents of the cannabis social clubs in Spain - Belackova, Vendula; Wilkins, Chris (The International journal on drug policy, 2018)
BACKGROUND: There is growing experience with the not-for-profit, consumer-driven cannabis social club (CSC) model that builds on self-supply, self-organization and harm-reduction; these are principles upon which people who use drugs (PWUD) have been engaging for decades. Recent legalization of cannabis in a number of jurisdictions and the related challenges in regulating production, sale, taxation and health-related matters have raised interest in non-commercial models of cannabis supply. The "codes of conduct" (CsoC) of CSC federations in Spain might reveal whether a consumer-based model could overcome these challenges. METHODS: To examine the content of the CSC auto-regulatory documents, an online search using key terms to identify the CsoC was conducted. Six documents were found; analysis of the main thematic categories and overarching themes was conducted. It was discussed how these corresponded to the areas of cannabis policy regulation and what the main limitations of the CSC model were. RESULTS: The CsoC detailed the rules for CSC administration, not-for-profit aims, "invitation only" and other conditions of membership, collective cultivation and security as well as for operation of the consumption venue and health-related initiatives. The themes in the CsoC overlapped with cannabis regulatory areas as outlined internationally. Concern over cannabis prices and potency was missing in the CsoC. The potential strengths of the CSC model might include safe environment for peer-delivered harm reduction practice, preventing illicit transactions, quality control, shifting economic surplus to the consumers and increased consumer responsibility. The limitations of the CSC model include high threshold, disguised motives, tax revenue and the risk of both under- and over-regulation. CONCLUSION: CSCs represent an opportunity to enhance consumer agency and responsibility. The right "to be self-supplied" with psychoactive substances can be granted to consumer associations - but authorities need to provide a framework to facilitate this voluntary self-organization, including minimum standards around public health and safety, and to involve consumers in the development of these regulations.
Keywords: kouření marihuany; účast komunity; lidé; spotřebitelské organizace; sebekontrola; Quality Control; řízení kvality; Marijuana Smoking; kontrola léčiv a omamných látek; Consumer Organizations; Humans; Self-Control; Community Participation; Drug and Narcotic Control